Impact of fear of COVID-19 on students' performance, moderating role of mindfulness: HSK students' perception-based view - Meiyi, Zhang; Liu, Yang (Frontiers in Public Health, 2022)
After suffering from the panademic, educational institutions have to swipe their academic activities from manual to the online pattern. The online education system may cause attitudinal and behavioral changes in students' learning patterns. With the support of stress theory, the present study is trying to determine the association of fear of panademic with students’ performance. In addition, the present study also attempts to determine the impact of fear of panademic on anxiety. Further, determining the association of anxiety with students’ performance is also an important objective of the current study. Moreover, this study also attempts to determine the mediating role of anxiety in the relationship between fear of panademic and students’ performance. This study also attempts to check the moderating role of mindfulness between fear of panademic and employee performance and between anxiety and employee performance, respectively. For empirical investigation, the current study collected the data from 320 HSK teachers from different colleges and universities in China. The present study applied partial least square structural equation modeling for the empirical investigation of hypotheses by using Smart PLS software. The present study's findings confirmed that fear of panademic negatively affects students’ performance and positively correlates with anxiety. The current study’s outcomes revealed that anxiety negatively affects students’ performance. The outcomes also confirmed that anxiety negatively mediates the relationship between fear of panademic and students’ performance. The present study's findings also acknowledged that mindfulness does not moderate the relationship between fear of panademic and employee performance and has a positive moderation between anxiety and employee performance, respectively. The present study's findings also offer important practical, theoretical, and managerial implications.